Interferensi Bahasa Indonesia Terhadap Bahasa Sunda Pada Podcast Sule Production - Sihombing, Kristi Anastasya; Emha, Ratna Juwitasari (CAKRAWALA LINGUISTA, 2024)
This study explains the interference in phonology and morphology that occurs on the Sule Production podcast on youtube. This research is a qualitative type of research. The data and data sources are in the form of Ariel's speech as a resource person in a podcast hosted by Sule on the Sule Production Youtube channel entitled "Only in Sulpod Ariel Noah Lucu". Data collection was carried out using the observation technique and continued with the recording technique. The data that has been collected is analyzed using the referential matching method. Data analysis was carried out with a sociolinguistic approach in the form of language interference, which is mutually influencing one language to another. The results were known that there was Sundanese interference in the speech in the Sule Production podcast. Phonological interference occurs in the form of phoneme changes, while morphological interference occurs in changes in the form of Indonesian verbs/verbs due to the influence of Sundanese suffixes and prefixes.